The fantastic adventures of Krishna - Demi (Wisdom Tales, 2013)
Sent by the God Vishnu to aid humanity in the eighth century BCE, a young Krishna hides among poor cowherds and uses miraculous powers to fight an evil demon king who has overthrown the peaceful kingdom of Mathura.